2022
DOI: 10.1097/rlu.0000000000004306
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Artery Angiomatoid Fibrous Histiocytoma Mimicking a Large Pulmonary Embolism

Abstract: A 39-year-old man presented with progressive dyspnea and lower extremity edema. Doppler ultrasound demonstrated bilateral leg partially occluded venous thromboses. A V/Q scan revealed a mismatched perfusion defect involving the entire right middle and lower lobes. Subsequent CT pulmonary angiogram revealed a mass lesion occluding the right interlobar pulmonary artery. Endobronchial ultrasound–guided fine-needle aspiration of the mass was concerning for neoplasm. 18F-FDG PET/CT demonstrated marked hypermetaboli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…It has also been reported that various radiation-induced sarcomas and subtypes may occur after radiotherapy 10,11. It has been shown in many studies that benign fibrous histiocytomas can show intense FDG uptake and mimic malignancy [12][13][14][15]. In this case, we would like to present that benign fibrous histiocytoma may develop after radiotherapy and may mimic recurrent disease.…”
mentioning
confidence: 86%
See 1 more Smart Citation
“…It has also been reported that various radiation-induced sarcomas and subtypes may occur after radiotherapy 10,11. It has been shown in many studies that benign fibrous histiocytomas can show intense FDG uptake and mimic malignancy [12][13][14][15]. In this case, we would like to present that benign fibrous histiocytoma may develop after radiotherapy and may mimic recurrent disease.…”
mentioning
confidence: 86%
“…10,11 It has been shown in many studies that benign fibrous histiocytomas can show intense FDG uptake and mimic malignancy. [12][13][14][15] In this case, we would like to present that benign fibrous histiocytoma may develop after radiotherapy and may mimic recurrent disease. Local recurrence and postradiotherapy sarcomas should be considered in the differential diagnosis of such an intensely hypermetabolic thoracic subcutaneous nodular lesion in patients with a history of ipsilateral breast cancer.…”
mentioning
confidence: 99%